2009
DOI: 10.1007/s00535-008-2293-3
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of reactive oxygen species in indomethacin-induced apoptosis of small intestinal epithelial cells

Abstract: Taken together, reactive oxygen species production is one of the mechanisms by which indomethacin induced small intestinal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 7 publications
3
44
0
Order By: Relevance
“…A similar decrease in TEER has been reported in another study, where human embryonic stem cell (hESC)-derived RPE cells and ARPE-19 cells were exposed to hydrogen peroxide. 31,32 These results are also in agreement with a previous study performed in our laboratory using the ARPE-19.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A similar decrease in TEER has been reported in another study, where human embryonic stem cell (hESC)-derived RPE cells and ARPE-19 cells were exposed to hydrogen peroxide. 31,32 These results are also in agreement with a previous study performed in our laboratory using the ARPE-19.…”
Section: Discussionsupporting
confidence: 83%
“…To investigate the ability of NACA to preserve BRB function, membrane integrity after TBHP exposure was evaluated using dextran permeability and TEER assays. 31 NACA prevented TBHP-induced reduction in TEER, verifying its ability to protect cellular homeostasis and outer BRB integrity under severe oxidative stress conditions. A similar decrease in TEER has been reported in another study, where human embryonic stem cell (hESC)-derived RPE cells and ARPE-19 cells were exposed to hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…This means that HSP70 can reduce oxidative stress and cell injury. Our group recently showed that ROS are involved in indomethacin-induced intestinal epithelial cell injury [23]. ROS are initiators of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that cyclooxygenase (COX)-dependent and COX-independent pathways were involved in this phenomenon, and we found that indomethacin significantly induced reactive oxygen species (ROS) production in small intestinal epithelial cells through a COX-independent pathway [10].…”
Section: Introductionmentioning
confidence: 95%